Contrast-enhanced MR angiography utilizing parallel acquisition techniques in renal artery stenosis detection - Slanina, Martin; Zizka, Jan; Klzo, Ludovít; Lojík, Miroslav (European journal of radiology, 2010)
Significant renal artery stenosis (RAS) is a potentially curable cause of renovascular hypertension and/or renal impairment. It is caused by either atherosclerosis or fibromuscular dysplasia. Correct and timely diagnosis remains a diagnostic challenge. MR angiography (MRA) as a minimally invasive method seems to be suitable for RAS detection, however, its diagnostic value widely differs in the literature (sensitivity 62-100% and specificity 75-100%). The aim of our prospective study was to compare the diagnostic value of contrast-enhanced MRA utilizing parallel acquisition techniques in the detection of significant RAS with digital subtraction angiography (DSA). A total of 78 hypertensive subjects with suspected renal artery stenosis were examined on a 1.5 Tesla MR system using a body array coil. Bolus tracking was used to monitor the arrival of contrast agent to the abdominal aorta. The MRA sequence parameters were as follows: TR 3.7 ms; TE 1.2 ms; flip angle 25 degrees; acquisition time 18s; voxel size 1.1 mm x1.0 mm x 1.1 mm; centric k-space sampling; parallel acquisition technique with acceleration factor of 2 (GRAPPA). Renal artery stenosis of 60% and more was considered hemodynamically significant. The results of MRA were compared to digital subtraction angiography serving as a standard of reference. Sensitivity and specificity of MRA in the detection of hemodynamically significant renal artery stenosis were 90% and 96%, respectively. Prevalence of RAS was 39% in our study population. Contrast-enhanced MRA with high spatial resolution offers sufficient sensitivity and specificity for screening of RAS.
Keywords: kontrastní látky; obstrukce renální arterie; senzitivita a specificita; Sensitivity and Specificity; Humans; Algorithms; lidé středního věku; Image Enhancement; Contrast Media; interpretace obrazu počítačem; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Organometallic Compounds; reprodukovatelnost výsledků; magnetická rezonanční angiografie; organokovové sloučeniny; Adult; Image Interpretation, Computer-Assisted; ženské pohlaví; Male; Reproducibility of Results; Middle Aged; algoritmy; Young Adult; Magnetic Resonance Angiography; mužské pohlaví; Renal Artery Obstruction; vylepšení obrazu